Experimental Research on a Frost-free Air Source Heat Pump - Qiu Junjun; Zhang Xiaosong; Li Weihao (Zhileng xuebao)
A novel air source heat pump systemthat operates efficiently during winter and improvesits performance during summer has been proposed. Based on the experimental results, the regeneration mode and regression analysis of the experimental data were obtained. The relative error of the two formulaswas relatively low, which exhibited a high degree of fitting. The average relative error of regeneration quantity and regeneration efficiency was 0.31% and 0.56%, respectively. Moreover, a correlation analysis was conducted to determine the effects of air volume flow rate, solution temperature, solution volume flow rate, and solution mass fraction on the regeneration performance of the system. The corresponding results demonstrated an increase in the regeneration rate with an increase in the outdoor air flow rate, solution temperature, and solution volume flow rate, and a decrease in the solution mass fraction. In addition, the regeneration efficiency increased by 26.00% and 13.63% with a decrease in the air volume flow rate andan increasein the solution volume flow rate, respectively. Within the scope of this study, regeneration rate demonstrated an increment of 26.30% with an increase in the solution volume flow rateand a decrement of 6.10% with an increase in solution mass fraction, respectively, whereas the solution temperature and mass fraction were found to have slight influence on it.